Boy, do not touch that plug: The table of drug use in Ecuador in the light of critical criminology. / Muchacho, no toques ese enchufe. La tabla de uso de drogas en el Ecuador a la luz de la criminología crítica - CASTRO ANIYAR, Daniel (Utopía y Praxis Latinoamericana, 2019)
Abstract: In Ecuador, some political operators achieved a legal disposition that allows high amounts of illicit substance consumption without addressing the other parts of the production and distribution chain. Although the defenders of the consumption table use sources of critical criminology, it is observed that such an approach is not relevant without addressing the context, that is: the criminal situation and the apparatuses of social control in operation. This article points out the danger of: a) allowing an undesirable increase of the criminal opportunity, b) erroneously assuming that the consumption table will lead to abolition, c) confusing the existence of a process of criminalization of the subordinate sectors with converting the delinquent in a political actor of democratic change. At the same time, several researchers indicated how the relationship between the decree of the tenure or consumption table and the increase in criminal activities took place. The theoretical problems of evaluating this policy are discussed in relation to the need to reinforce empirical and situational studies within critical criminology. Resumen: En Ecuador, algunos operadores políticos lograron el decreto de una disposición que permite altas cantidades de consumo de sustancias ilícitas sin atender las otras partes de la cadena. Si bien los defensores de la tabla de consumo utilizan fuentes de la criminología crítica, se observa que tal enfoque no es pertinente sin abordar el contexto, esto es: la situación delictiva y los aparatos del control social en funcionamiento. Este artículo señala el peligro de: a) permitir un aumento no deseable de la oportunidad criminal, b) asumir erróneamente que la tabla de consumo llevará a la abolición, c) confundir la existencia de un proceso de criminalización de los sectores subordinados con convertir al delincuente en un actor político del cambio democrático. Al mismo tiempo, varios investigadores indicaron cómo se producía la relación entre el decreto de la tabla de tenencia o consumo y el aumento de las actividades delictivas. Los problemas teóricos de la evaluación de esta política se discuten en relación con la necesidad de reforzar los estudios empíricos y situacionales dentro de la criminología crítica.